The Influence of Human Resource Development and Work Discipline on Teacher Peformance Goverment Employees With an Agreement Work (PPPK) at SMK Negeri 5 Gowa - Sahariah; Mugnhi Latifah; Muhtazib (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This study aims to determine the effect of Human Resource Development and Work Discipline on Teacher Peformance Goverment Employees with an Agreement Work (PPPK) at SMK Negeri 5 Gowa. This type of research is quantitative research with multiple linear regression. The results of this study indicate that Human Resources (X1) has a positive effect on employee performance with a significance value of 0.003 at a significance level of 0.05. Work discipline (X2) has a positive effect on employee performance with a significance value of 0.000 at a significance level of 0.05. By looking at these results, it can be concluded that the variable human resources (X1) and work discipline (X2) on employee performance (Y) simultaneously affect the dependent variable.